Persepsi Ibu Hamil tentang Terapi Komplementer dalam Kehamilan - Fatihatul Hayati (Jurnal Akademika Baiturrahim Jambi, 2021)
Complementary therapy has been applied in various regions to accompany conventional / medical therapy. Pregnant women are a group that is encouraged to take advantage of complementary therapy or medicine in dealing with their perceived complaints, because complementary therapy can avoid the side effects of conventional medicine and have great control over their own health. The purpose of this study was to determine the perceptions of pregnant women about complementary therapies in pregnancy. This research is a quantitative study with a cross sectional approach. Primary data collection research using a questionnaire. The population in this study were all pregnant women at PuskesmasPutri Ayu Jambi City with a sample of 88 people. The sampling technique is accidental sampling. Data analysis was carried out by univariate. From the results of the research on the perceptions of pregnant women about complementary therapies in pregnancy, it was concluded that most pregnant women had a positive perception, namely 73.3%. The results of this study are expected to contribute to increasing the knowledge of pregnant women about complementary therapies that are safe for pregnant women, so that pregnant women can achieve optimal health by utilizing non-pharmacological therapies and the fetus can grow healthy